Tanzania: Joint sector review assessment: Advancing mutual accountability through comprehensive, inclusive, and technically robust review and dialogue - Ministry of Agriculture, Food Security, and Cooperatives, Tanzania (Government of Tanzania, Ministry of Agriculture, Food Security, and Cooperatives, 2014)
The joint sector review (JSR) assessment exercise was undertaken in Tanzania from March to May 2014 to evaluate progress in Tanzania under CAADP and, in particular, progress on implementation of TAFSIP. This report was produced under the leadership of the Ministry of Agriculture, Food Security, and Cooperatives (MAFC). The Regional Strategic Analysis and Knowledge Support System (ReSAKSS) office for Eastern and Central Africa supported national collaborators to undertake the review. The assessment drew information from desk reviews, interviews with key stakeholders in the agricultural sector of Tanzania, and brainstorming and building consensus on the opportunities and challenges facing Tanzania’s agricultural sector through two stakeholder workshops.